Acute Hypercapnia/Ischemia Alters the Esterification of Arachidonic Acid and Docosahexaenoic Acid Epoxide Metabolites in Rat Brain Neutral Lipids. Issue 1 (6th November 2019) - Otoki, Yurika; Metherel, Adam H.; Pedersen, Theresa; Yang, Jun; Hammock, Bruce D.; Bazinet, Richard P.; Newman, John W.; Taha, Ameer Y.
Abstract: In the brain, approximately 90% of oxylipins are esterified to lipids. However, the significance of this esterification process is not known. In the present study, we (1) validated an aminopropyl solid phase extraction (SPE) method for separating esterified lipids using 100 and 500 mg columns and (2) applied the method to quantify the distribution of esterified oxylipins within phospholipids (PL) and neutral lipids (NL) (i.e. triacylglycerol and cholesteryl ester) in rats subjected to head‐focused microwave fixation (controls) or CO2 ‐induced hypercapnia/ischemia. We hypothesized that oxylipin esterification into these lipid pools will be altered following CO2 ‐induced hypercapnia/ischemia. Lipids were extracted from control ( n = 8) and CO2 ‐asphyxiated ( n = 8) rat brains and separated on aminopropyl cartridges to yield PL and NL. The separated lipid fractions were hydrolyzed, purified with hydrophobic–lipophilic–balanced SPE columns, and analyzed with ultra‐high‐pressure liquid chromatography coupled to tandem mass spectrometry. Method validation showed that the 500 mg (vs 100 mg) aminopropyl columns yielded acceptable separation and recovery of esterified fatty acid epoxides but not other oxylipins. Two epoxides of arachidonic acid (ARA) were significantly increased, and three epoxides of docosahexaenoic acid (DHA) were significantly decreased in brain NL of CO2 ‐asphyxiated rats compared to controls subjected to head‐focused microwave fixation. PL‐bound fatty acid epoxides were highly variable and did not differ significantly between the groups. This study demonstrates that hypercapnia/ischemia alters the concentration of ARA and DHA epoxides within NL, reflecting an active turnover process regulating brain fatty acid epoxide concentrations.